2014
DOI: 10.1088/0957-4484/25/50/504007
|View full text |Cite
|
Sign up to set email alerts
|

Atomic layer deposition of lithium phosphates as solid-state electrolytes for all-solid-state microbatteries

Abstract: Atomic layer deposition (ALD) has been shown as a powerful technique to build three-dimensional (3D) all-solid-state microbattery, because of its unique advantages in fabricating uniform and pinhole-free thin films in 3D structures. The development of solid-state electrolyte by ALD is a crucial step to achieve the fabrication of 3D all-solid-state microbattery by ALD. In this work, lithium phosphate solid-state electrolytes were grown by ALD at four different temperatures (250, 275, 300, and 325 °C) using two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
104
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(117 citation statements)
references
References 48 publications
(89 reference statements)
11
104
2
Order By: Relevance
“…Li 3 PO 4 can be deposited using either LiO t Bu or LiHMDS as the lithium source and TMPO (trimethyl phosphate, Figure 9) as the phosphate precursor [114,115]. The LiO t Bu + TMPO process showed a constant growth rate of approximately 0.7 Å/cycle between 225 and 275 • C [114].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Li 3 PO 4 can be deposited using either LiO t Bu or LiHMDS as the lithium source and TMPO (trimethyl phosphate, Figure 9) as the phosphate precursor [114,115]. The LiO t Bu + TMPO process showed a constant growth rate of approximately 0.7 Å/cycle between 225 and 275 • C [114].…”
Section: Methodsmentioning
confidence: 99%
“…Regardless of the lithium precursor, the phosphate films crystallized into the orthorhombic Li3PO4 phase during HTXRD measurements. Wang et al [115] and Létiche et al [116] have studied the Li3PO4 process using LiO t Bu and TMPO in an effort to measure the lithium-ion conductivity of these films. Wang et al reported an increasing growth rate as a function of the deposition temperature at 250-325 °C, which might be a result of the somewhat unsaturative behaviour of the process [114].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Li 3 PO 4 has been widely used by many commercial all-solid-state battery manufacturers due to the relatively high Li-ion conductivity and (electro)chemical stability with respect to metallic Li anodes [40]. Some methods have been described to deposit thin films of Li 3 PO 4 , including pulsed laser deposition [41,42], atomic layer deposition (ALD) [43], E-beam evaporation [44] and sputter deposition [45,46] . Figure 1(a) shows the deposition thickness of Li 3 PO 4 thin films as a function of time at different temperatures by MOCVD, using tert-butyllithium (t-BuLi) as Li-precursor and trimethyl phosphate(TMPO) as P-precursor [47].…”
Section: Solid-state Electrolytesmentioning
confidence: 99%
“…Crystalline Li 3 PO 4 on the other hand only provides a conductivity of 10 -18 S/cm. Recently, ALD depositions of both Li 3 PO 4 and LiPON have been reported in literature (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%